Changing Epidemiology of Extended-Spectrum β-Lactamases in Argentina: Emergence of CTX-M-15 - Sennati, S. (2012)
A multicenter survey, carried out in 2010 in Argentina, showed an increased prevalence of extended-spectrum p-lactamase (ESBL)-producing enterobacteria, with some changes in the molecular epidemiology of circulating ESBLs. While enzymes of the CTX-M-2 group remain endemic, the emergence of CTX-M-15 and of enzymes of the CTX-M-8 and CTX-M-9 groups was observed. The CTX-M-15-positive isolates represented 40% of CTX-M producers and included representatives of Escherichia coli ST131 and Klebsiella pneumoniae ST11.